Effect Of Recycling On The Mechanical Properties Of Polylactic Acid (Pla)-Impact Modifier Blend - Rosli, Muhammad Syamil (Universiti Sains Malaysia, 2017)
The research on the effect of recycling on the mechanical properties of polylactic acid (PLA)/impact modifier blend was conducted to study and investigated the influenced of recycling on the mechanical and thermal properties of PLA. PLA were prepared using extrusion process followed by injection molding. The properties of PLA and PLA blend with an impact modifier were characterized by tensile test, impact test, melt flow analysis (MFI), differential scanning calorimetry (DSC) analysis, and thermogravimetric analysis (TGA). Recycling PLA slightly reduced the mechanical properties and the increasing trend shown by melt flow rate indicates the decreased in viscosity of PLA as the number of recycling increased. Besides, the thermal decomposition temperature of PLA decreased as the number of recycling increased due to thermal degradation and reduced the molecular weight including weakening the thermal resistance of PLA. DSC analysis shows slightly decreased in glass transition temperature (Tg) for PLA and PLA blends upon recycling. Incorporation of PLA with an impact modifier is partially compatible to PLA and imparts the rubbery phase to PLA thus increase the flexibility chain movement of PLA. Thus, PLA changed a rubbery phase at the lower temperature and hence the Tg will be lower than pure PLA. Nevertheless, the degree of crystallinity of PLA blend with an impact modifier literally higher as to compare with pure PLA due to the reduction of enthalpy of fusion of PLA.